KOMUNIKASI ANTARBUDAYA DALAM PROSES ADAPTASI MAHASISWA IPB ASAL BALI DI KOTA BOGOR - Faisal, M.Fadli; Moenawar, Mohamad Ghozali; Riyanto, Sutisna; Dharmawan, Leonard; Manisya, Nabhila; Azzahra, Maharani (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
Intercultural communication and cultural adaptation are crucial concepts in social interaction within multicultural societies. Intercultural communication refers to the exchange of information, values, and norms between individuals from different cultural backgrounds. Cultural adaptation is a process of self-adjustment carried out by individuals when encountering a new cultural environment, which involves changes in the way they communicate, think, and act. In the educational context, students from diverse cultures often face challenges in communicating and adapting to the campus culture. This research aims to analyze the adaptation process and intercultural communication of IPB students from Bali in Bogor City, as well as identify the obstacles they face in adapting and communicating. The research employs a qualitative descriptive method, gathering data through in-depth interviews and literature review. The results reveal that students from Bali experience several stages of adaptation to the culture and habits of the people in Bogor. The obstacles they encounter include differences in culture, language, food preferences, access to places of worship, and differences in values and social norms. Despite these challenges, IPB students from Bali demonstrate the ability to adapt to these cultural differences using various communication strategies. These students have undergone several phases, including excitement about a new culture, culture shock, recovery, and ultimately cultural adjustment. This research highlights the importance of understanding intercultural communication in supporting the adaptation process of students from diverse cultural backgrounds.